Determination of cardiac output by Doppler echocardiography. Issue 1 (January 1984) - Ihlen, H; Amlie, J P; Dale, J; Forfang, K; Nitter-Hauge, S; Otterstad, J E; Simonsen, S; Myhre, E
Abstract : Cardiac output determined by Doppler echocardiography was compared with that determined by thermodilution at rest and during dobutamine infusion in 10 patients (group A) and by the Fick method at rest in 11 patients (group B). All patients had angina pectoris without valvular heart disease. Maximum spatial blood velocity and cross sectional aortic area were estimated by the Doppler technique and echocardiography. Cardiac output was calculated by multiplying blood velocity by aortic area at various levels in the ascending aorta. The best correlation of cardiac output between the invasive and non-invasive methods was obtained when maximum velocity in the aortic root and the aortic orifice area were used in the calculations. Cardiac output was considerably overestimated when area measurements in the aortic root were used.